2018
DOI: 10.1016/j.ijpharm.2018.04.032
|View full text |Cite
|
Sign up to set email alerts
|

PAMAM dendrimers as a carbamazepine delivery system for neurodegenerative diseases: A biophysical and nanotoxicological characterization

Abstract: Carbamazepine (CBZ) is an antiepileptic drug, which also could be used in the treatment of neurodegenerative diseases, such as the Alzheimer's disease. However, its use has been limited due to its low solubility, inefficient pharmacokinetic profiles, and multiple side effects. PAMAM dendrimers, ethylenediamine core, generation 4.0 (amine terminal groups) and 4.5 (carboxylate terminal groups) (DG4.0 and DG4.5 respectively) are polymers that can increase drug solubility through complexation. Thus, the aim of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(38 citation statements)
references
References 69 publications
2
35
0
Order By: Relevance
“…Drug release from the carbamazepine‐dendrimer conjugates was found to be controlled, and the developed formulations were less toxic than free carbamazepine in vitro and in vivo. Recently, a new type of dendrimer consisting of a core composed of poly(propylene imine) and a maltose–histidine shell (G4HisMal) was developed by Azo et al . to protect transgenic mice against AD‐induced memory loss, to enhance BBB penetration and to improve biocompatibility.…”
Section: Emerging Researches In Nanotechnology Related To Admentioning
confidence: 99%
“…Drug release from the carbamazepine‐dendrimer conjugates was found to be controlled, and the developed formulations were less toxic than free carbamazepine in vitro and in vivo. Recently, a new type of dendrimer consisting of a core composed of poly(propylene imine) and a maltose–histidine shell (G4HisMal) was developed by Azo et al . to protect transgenic mice against AD‐induced memory loss, to enhance BBB penetration and to improve biocompatibility.…”
Section: Emerging Researches In Nanotechnology Related To Admentioning
confidence: 99%
“…Since the PAMAM dendrimer itself is extremely water-soluble, encapsulation within the cavities is an ideal way to solubilize poorly water-soluble drugs in aqueous solutions. For example, Igartúa and colleagues found that a G4 PAMAM dendrimer with an amine surface (or a G4.5 PAMAM dendrimer with a carboxyl surface) could encapsulate about 20 molecules of the anti-epileptic drug, carbamazepine, which has potential for treating neurodegenerative diseases [ 30 ]. Recent reviews on the use of PAMAM dendrimers for encapsulating drugs are available [ 5 , 31 ].…”
Section: Features Of Pamam Dendrimers Useful For Neuroscience Applmentioning
confidence: 99%
“…However, it is poorly soluble in water and shows unpredictable pharmacokinetic profiles. Generation 4.5 carboxyl-terminated dendrimers were loaded with CBZ to yield stable, soluble and safe (as tested on RBCs and zebrafish) formulations for potential applications in the treatment of neurodegenerative diseases associated with toxicity of aggregated proteins such as Alzheimer’s disease, amyotrophic lateral sclerosis, Huntington’s disease and Parkinson’s disease [ 30 ]. No further studies were performed to see if the CBZ-dendrimer formulations were effective for the treatment of these diseases.…”
Section: Delivery Of Small Moleculesmentioning
confidence: 99%
“…The spontaneous movement was studied in a multichannel analog to digital converter system (WMicrotracker, Designplus SRL, Argentina) as we previously described (Igartúa et al, 2015;Igartúa et al, 2018). Activity events were recorded for 15 min at 1, 4, 24, and 48 hpi, at room temperature.…”
Section: Zebrafish Larvae: Neurotoxicitymentioning
confidence: 99%